PEMBERDAYAAN KADER DAN KELUARGA LANSIA DENGAN HIPERTENSI DALAM PENCAPAIAN LANSIA SEHAT MELALUI POSYANDU LANSIA DI SURABAYA (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Hypertension is a disease that causes premature death especially among the elderly. However, the awareness and participation of the elderly are still low in efforts to control hypertension. Cadres and families have roles as companions for the elderly in carrying out activities, meeting daily needs, and providing access to good health services for the elderly. Therefore, it is essential to convey helpful information to cadres and families. However, no media can facilitate appropriate information that can be used at this time. This study is interested in doing a health information module to increase the empowerment of cadres to achieve healthy elderly in the community. Two stages have been carried out in the implementation. First, there is the preparation in the form of modules, and the second is socialization or training to the audience. The knowledge evaluation process was carried out using a questionnaire consisting of 10 questions related to hypertension information and elderly care. The analysis was performed by paired t-test. The results showed differences in participants' knowledge before and after being given community socialization (p-value of 0.000). The results of this evaluation indicate that socialization can increase participants' knowledge. Therefore, it is recommended to include education activities into community as part of healthy initiative. Keywords: elderly; hypertension; integrated healthcare center